Aspects of Validity in Large-Scale Programs of Student Assessment - Wilson, Robert J. (Alberta Journal of Educational Research, 1999)
Large-scale programs of student assessment have increased in number and scope over the last two decades. Their approaches were largely derived from the technology developed for standardized achievement testing in the United States. Because large-scale assessment purposes are more extensive than testing purposes, the validity issues are more complex. This article explores what those differences are in such areas as item types, administration, interpretation, and standards. It concludes with some recommendations concerning the questions that need to be addressed if large-scale assessments are to accomplish their varied goals adequately.